Environmental perceptions of cloud forest conservation in three mestizo communities of Sierra Madre Oriental, Mexico - Castillo-Trujillo, Yoatzin; Pavón, Numa; Pulido-Silva, Maria Teresa; Ortiz-Pulido, Raúl (Ethnobiology and Conservation, 2026)
Cloud forests are highly biodiverse ecosystems currently at risk of disappearing due to agricultural and livestock expansion. Local communities have traditionally relied on them for firewood, timber, food, and water, and other resources. Conservation strategies have often focused on establishing protected areas, yet these initiatives frequently neglect the social component, leading to community rejection and limited success. In contrast community-based conservation emphasizes the role of local people as the main promoters of biodiversity protection. A first step toward implementing such strategies is to assess environmental perception within local populations. This study examined environmental perception in three mestizo communities located in a cloud forest area of the Sierra Madre Oriental, México, through semi-structured interviews. Respondents expressed affection for the forest but did not consider it an economically valuable resource. They acknowledged specific benefits, particularly the provision of firewood, but displayed aversion toward wildlife, especially snakes. Overall, participants showed little concern for forest conservation and demonstrated reluctance to engage in environmental programs, prioritizing productive projects that provide immediate economic returns. Currently, forest persistence in the region appears to be more strongly influenced by external factors, such as agricultural abandonment driven by migration, than by deliberate conservation actions. These findings highlight that before introducing new conservation initiatives, it is essential to inform and raise awareness among local communities about the broader social and economic benefits associated with maintaining cloud forest. Strengthening this understanding could encourage local participation and help ensure the long-term sustainability of these ecosystems.